Revisiting the conservation genetics of Pampas deer (Ozotoceros bezoarticus) - Gonzalez, Susana; Repetto, Leticia; Gutiérrez, Verónica; Olivera, María Eugenia; Corbi Botto, Claudia; Leone, Yanina; Merino, Mariano L.; Góss Braga, Fernanda; Barbanti Duarte, José Mauricio; Maldonado, Jesús Eduardo; Cosse, Mariana (THERYA, 2024)
The Pampas deer (Ozotoceros bezoarticus) is a unique species of neotropical cervid, that inhabits a wide range of open habitats including grasslands, pampas, savannas, and cerrado (Brazil) from -5° to -41° S. The reduction of the area encompassed by these habitats has been dramatically reduced to less than 2 % by human activities such as agriculture, urbanization, and poaching. Three decades ago, we initiated a molecular genetic study of the Pampas deer based on representative samples from throughout their geographic range. Our aim is to reevaluate the effect that habitat fragmentation has had on gene flow among eight wildlife Pampas deer populations and one from the captive breeding centre Estación de Cría de Fauna Autóctona (ECFA). We examined DNA sequences from three mitochondrial markers: the control region (D-loop), Cytochrome b (Cytb), and Cytochrome Oxidase I (COI). Furthermore, we compared the resolution of the different mitochondrial markers to elucidate the phylogenetic and phylogeographic patterns of the species to define Evolutionary Significant Units (ESU`s). The amount of gene flow was correlated with geographic distance among groups and populations and was consistent with limited dispersal being the primary determinant of genetic differentiation between populations. Our results showed that the D-loop was the most appropriate marker for defining Evolutionary Significant Units. We found that the critically endangered Paraná population showed significant genetic distance from the others and revealed unique haplotypes with all the mitochondrial markers. The molecular genetic results provide a mandate for habitat restoration and design a management plan to conserve these relictual populations.